The soils of Greece - Yassoglou, Nicholas; Tsadilas, Christos; Kosmas, Costas (Springer, 2017)
This book presents a comprehensive and up-to-date overview on soils of Greece. It includes sections on soil research history, climate, geology, geomorphology, major soil types, soil maps, soil properties, soil classification, soil fertility, land use and vegetation, soil management, soils and humans, soils and industry, future soil issues. The book summarizes what is known about the soils in Greece in a concise and highly reader-friendly way.
Keywords: Soils -- Greece.; Greece.; elektronické knihy; electronic books